Channel Widening Downstream of Valley Gorges Influenced by Flood Frequency and Floodplain Roughness. Issue 1 (24th January 2019) - Croissant, Thomas; Lague, Dimitri; Davy, Philippe
Abstract: Mountain fronts are the locus of significant variations in river width characterized by narrow bedrock gorges opening to wider unconfined alluvial rivers that are often braided. The contribution of the abrupt change in river valley confinement in modulating the long‐term transport capacity and the resulting equilibrium channel width has never been considered. Here we use a numerical model integrating the full frequency‐magnitude distribution of streamflow to explore the long‐term bedload transport capacity of idealized confined and unconfined channels, both single thread and braided. The model predicts a significant transport capacity loss for a single channel of constant width at the transition between confined gorges and unconfined floodplains that is slightly reduced when floodplain vegetation is present. Because the total transport capacity of a single‐thread channel systematically decreases with channel width in a stochastic framework, only narrower unconfined channels could compensate for the loss of confinement. This prediction contradicts observations of widening ratios ranging from three to eight downstream of gorges in various world rivers. We resolve this inconsistency by demonstrating that a braided river made of narrow channels inset in a wide floodplain can maintain the total bedload transport capacity downstream of gorges by increasing the range of competent discharges. We also show that riparian vegetation may only enhance bedload transport capacity for highly variable discharge regimes and discuss the relevance of various definitions of representative discharges. These results point to the previously unrecognized role of valley confinement in modulating the sediment transport capacity of rivers. Key Points: Flood frequency and valley confinement have a dominant effect on long‐term bedload transport capacity Floodplain vegetation only increases long‐term bedload transport capacity for variable climate regimes Braided river regime is a means to maintain long‐term transport capacity at bedrock gorge/alluvial plain transition